Internalisasi Nilai Resolusi Konflik Tanpa Kekerasan : dalam Pembelajaran Sejarah dari Konflik Petani Jenggawah 1998 - Guruh Prasetyo (Education & Learning, 2025)
The 1998 Jenggawah agrarian conflict reflected the inequality of land ownership and the impact of non-inclusive development policies from the colonial era to the New Order. This study aims to analyze the transformation of peasant resistance from physical to symbolic and internalize the value of non-violent conflict resolution in history learning. Using a descriptive qualitative approach, data were collected through documentation and literature studies and then analyzed using qualitative data strategies. The results show that the change in the Reformation regime and peasant awareness encouraged a shift in struggle strategies towards dialogue and negotiation, culminating in the 1998 right to cultivate (Hak Guna Usaha) release agreement. This case proves that conflict resolution can be achieved without violence, providing a pedagogical foundation for teaching conflict dynamics, social transformation, and non-violent approaches to justice. Learning history through this case study facilitates the internalization of the value of non-violent conflict resolution, equips students with an understanding that conflict is dynamic and can be changed through constructive strategies, and develops empathetic and critical characters.